Antecedents and historical evolution, about the developed work of the Permanent Seminary of Nursing History in Asturias - Carmen Chamizo Vega (Universidad de Alicante, 2012)
In this work the author describes the evolution of the permanent seminary of nursing history of Asturias (Spain).